Development and validation of a video-based passing decision-making test for soccer and futsal - Gioldasis, A.; Mitrotasios, M.; Smirniotou, A. (Baltic Journal of Sport and Health Sciences, 2024)
Background: Success in team sports such as soccer and indoor soccer depends heavily on the ability to make accurate and quick decisions due to the dynamic and unpredictable nature of game conditions. This study aimed to create and verify a video-based test that evaluates decision making abilities in players participating in soccer and futsal (VPD SocFut).